An assessment of the environmental and socio-economic impacts of alien rabbits and hares - Tom Allmert; Jonathan M. Jeschke; Thomas Evans (Ambio, 2022)
Directly comparable data on the environmental and socio-economic impacts of alien species informs the effective prioritisation of their management. We used two frameworks, the Environmental Impact Classification for Alien Taxa (EICAT) and Socio-Economic Impact Classification for Alien Taxa (SEICAT), to create a unified dataset on the severity and type of impacts caused by alien leporids (rabbits and hares). Literature was reviewed to collate impact data, which was categorised following EICAT and SEICAT guidelines. We aimed to use these data to identify: (1) alien leporid species with severe impacts, (2) their impact mechanisms, (3) the native species and local communities vulnerable to impacts and (4) knowledge gaps. Native species from a range of taxonomic groups were affected by environmental impacts which tended to be more damaging than socio-economic impacts. Indirect environmental impacts were particularly damaging and underreported. No impact data were found for several alien leporid species.